Evaluation of IT Governance at Islamic Boarding Schools in the Special Region of Yogyakarta based on the COBIT 5 Framework - M. Sa’id Abdurrohman Kunta Mardlian; Muhammad Taufiq Nuruzzaman; Shofwatul 'Uyun; Bambang Sugiantoro (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Nowdays, almost all aspects of company operations are supported by information technology systems. Many pesantren have utilized information technology in supporting operational activities such as: using computers, accessing the internet, having a website, and managing information technology systems. The purpose of this study is to implement the COBIT 5 framework in the DSS (Deliver, Service, Support) domain in evaluating information technology governance and calculate the capability level value and gap analysis at Islamic Boarding Schools. The results of the Capability Level Analysis in the COBIT 5 DSS Domain obtained from 42 Islamic Boarding Schools showed that DSS01, DSS02, and DSS03 on average were at level 2, DSS04, DSS05, DSS06 on average at level 1. The results of the Gap Analysis in the COBIT 5 DSS Domain show that in DSS01, DSS02, and DSS03 the average GAP is 3, in DSS04, DSS05, and DSS06 the average GAP is 4. The result shows that Information Technology Governance in Islamic Boarding Schools in the Special Region of Yogyakarta based on an assessment with the COBIT 5 Framework is still low status and needs to be improved, as evidenced by the low Capability Level Value and the high GAP Value.